Combined tetraphenylethylene fluorogens with positive charge for imaging capsule-covered pathogens. Issue 20 (6th August 2020) - Ai, Wenting; Yang, Zhiqiang; Ma, Yufan; Han, Xiaomin; Chen, Yuzhi; Zhu, Kui; Wang, Zhuo
Abstract : We developed four positively charged tetraphenylethylene derivatives (PC-TPEgens) that in certain combinations were applied to identify capsule-bearing pathogens using fluorescence imaging. Abstract : Capsule-covered pathogens can cause serious infectious diseases, and are highly pathogenic to humans. Herein, we developed four positively charged tetraphenylethylene derivatives (PC-TPEgens) that in certain combinations were applied to identify capsule-bearing pathogens using fluorescence imaging. The dual-charged probes were used to visualize the entire process of phagocytosis of pathogens into macrophages.